Optimizing measurement of vision-related quality of life: a computerized adaptive test for the impact of vision impairment questionnaire (IVI-CAT). - Fenwick, Eva K.; Loe, Bao Sheng; Khadka, Jyoti; Man, Ryan E. K.; Rees, Gwyn; Lamoureux, Ecosse L. (Quality of Life Research, 2020)
Purpose: To compare the results from a simulated computerized adaptive test (CAT) for the 28-item Impact of Vision Impairment (IVI) questionnaire and the original paper-pencil version in terms of efficiency (main outcome), defined as percentage item reduction.Methods: Using paper-pencil IVI data from 832 participants across the spectrum of vision impairment, item calibrations of the 28-item IVI instrument and its associated 20-item vision-specific functioning (VSF) and 8-item emotional well-being (EWB) subscales were generated with Rasch analysis. Based on these calibrations, CAT simulations were conducted on 1000 cases, with 'high' and 'moderate' precision stopping rules (standard error of measurement [SEM] 0.387 and 0.521, respectively). We examined the average number of items needed to satisfy the stopping rules and the corresponding percentage item reduction, level of agreement between person measures estimated from the full IVI item bank and from the CAT simulations, and item exposure rates (IER).Results: For the overall IVI-CAT, 5 or 9.7 items were required, on average, to obtain moderate or high precision estimates of vision-related quality of life, corresponding to 82.1 and 65.4% item reductions compared to the paper-pencil IVI. Agreement was high between the person measures generated from the full IVI item bank and the IVI-CAT for both the high precision simulation (mean bias, - 0.004 logits; 95% LOA - 0.594 to 0.587) and moderate precision simulation (mean bias, 0.014 logits; 95% LOA - 0.828 to 0.855). The IER for the IVI-CAT in the moderate precision simulation was skewed, with six EWB items used > 40% of the time.Conclusion: Compared to the paper-pencil IVI instrument, the IVI-CATs required fewer items without loss of measurement precision, making them potentially attractive outcome instruments for implementation into clinical trials, healthcare, and research. Final versions of the IVI-CATs are available.